Ambito de acción, uso del hábitat y actividad diaria de la taltuza Orthogeomys heterodus (Rodentia: Geomyidae) en una zona hortícola de Costa Rica - Bonino, Never (1994)
Heme range, daily activity and habitat use of four Giant Pocket Gophers Orthogeomys heterodus were detennined by radlotelemetry. The study was carried out in a horticultural area of Cartago province, Costa Rica, during December 1989 and January 1990. Horne range averaged 325 m2 for males and 233 m2 for females. There was a signíficant relationship between borne range size and individual body mass. In average, 78 % of localizations were in the nest or refuge located in all cases in the border oí crops. Activity was greatest from 0600 lO 0800 ti and 1200 lO 1400 h, and was reduced at night